Analysis of bacterial biodiversity and ecological risk evaluation of organophosphorus in Lianhuan Lake - Shang Yang; Ran Wang; Wei Zhao (PLoS ONE, 2025)
Shallow lakes are vital water resources, playing key roles in water conservation, landscape management, and drinking water supply. However, recent years have seen significant challenges in their ecological protection. Lianhuan Lake is selected as the study area. Water quality characteristics are evaluated using the eutrophication index (TLI), water quality index (WQI) and integrated water quality index (IWQI). High-throughput sequencing (HTS) is employed to analyze microbial diversity and community composition, while gas chromatography (GC) was used to identify commonly used organophosphorus pesticides—including suprofos, coumaphos, prothiophos and mevinphos. Ecological Structure-Activity Relationships (ECOSAR), the Toxicity Estimation Software Tool (T.E.S.T.) and the Risk Quotient (RQ) are used to evaluate the ecological safety of Lianhuan Lake. The results indicate that the water quality of the Lianhuan Lake is class V, mildly eutrophic. A total of 1,062 microbial genera are identified in the sediments and water samples. The order of influence of water quality indicators on bacterial diversity is pH > TP > DO > TN > NH3-N > NO2-N > WT. Ten distinct organic phosphorus contaminants are detected. Nine of these compounds exhibited varying degrees of acute and chronic toxicity to fish, daphnia, and algae. Suprofos, coumaphos and prothiophos are highly toxic to daphnia. Suprofos, mevinphos and prothiophos have high ecological risk. These findings not only provide critical insights for the targeted management and pollution control of Lianhuan Lake but also underscore the need for monitoring organophosphorus pesticide residues in shallow lakes worldwide to protect aquatic ecosystems.